Kulturna in jezikovna dediščina Hijacinta Repiča, frančiškana pri sv. Ani v Kopru - Košir, Diana (Annales. Series historia et sociologia, 2023)
In the 19th century, the Franciscans were the most numerous order in Slovenia and extremely popular in the local area, working among the faithful in the cities and in the countryside with liturgy, pastoral care and educational work. In a linguistically mixed environment like Istria, they were important for the communication in Slovene language. The Franciscan monastery of St. Anne in Koper belonged to the Istrian-Dalmatian province before the First World War, and Slovenian, Croatian, and Italian monks lived there. Amongst them, the most active was Father Hijacint Repič (1863–1918), novice master, librarian, archivist and chronicler, author of numerous pious articles and of the Grammar of the Slovene language, which has not survived to this day. The article gives an overview of the Franciscan’s written legacy, especially the archival sources found in the Archives of the Central Library of Koper, in the Provincial Archive of Koper, in the Archive of the Monastery of St. Anne and in Provincial Archives in Venice, Ljubljana and Pula. By analysing primary and secondary sources, the author attempts to describe Father’s legacy and places it in the context of Slovenehood in Istria at the turn of the 20th century. The correspondence in several languages and with people from different social classes shows his broad social network and his personal criticism of contemporary events. The study presents the personality and work of Father Hijacint Repič, who, from a cultural-historical point of view, can be recognised as the bearer of Slovenian national and linguistic consolidation in Istria.
Keywords: archive; archivio; Arhivi; francescani; Franciscans; frančiškani; letteratura slovena; Monastero di Sant’Anna a Capodistria; Monastery of Saint Anne in Koper; pater Hijacint Repič; religious press; samostan sv. Ane v Kopru; Samostani; Slovenian literature; Slovenska književnost; stampa religiosa; Verski tisk; Zgodovina